2021
DOI: 10.1177/03611981211027880
|View full text |Cite
|
Sign up to set email alerts
|

Examining Driver Compliance with a Move-Over/Slow Down Law in Consideration of Vehicle Type and Messages Displayed on Upstream Dynamic Message Signs

Abstract: Move-over laws are intended to enhance the safety of road agency and law enforcement personnel who are working on or near the roadway. This study examined driver behavior through a series of field studies where these types of vehicles were located on the outside shoulder of a freeway with their lights activated. The study also evaluated the use of upstream dynamic message signs (DMS) to discern whether targeted safety messages had any impact on behavior under this scenario. Upstream and downstream speed and la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…However, the results again did not indicate any observable pattern with respect to the specific messages that were displayed on the roadside DMS. This was similar to a previous study that showed drivers were more likely to move over when law enforcement vehicles were present on the shoulder, but no clear patterns were observed among four different message types that were evaluated ( 15 ).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…However, the results again did not indicate any observable pattern with respect to the specific messages that were displayed on the roadside DMS. This was similar to a previous study that showed drivers were more likely to move over when law enforcement vehicles were present on the shoulder, but no clear patterns were observed among four different message types that were evaluated ( 15 ).…”
Section: Resultssupporting
confidence: 89%
“…In another study, message type was shown to have minimal impact on the rate of driver compliance with a move-over law requiring motorists to reduce their speeds and provide space when passing emergency and service vehicles on the roadside. This same study showed that compliance rates were higher when the roadside vehicle was a police car as opposed to a transportation maintenance vehicle, which suggests a potential synergistic effect between enforcement and messaging campaigns ( 15 ).…”
mentioning
confidence: 97%
“…For example, some studies have found little or no change in seat belt use or speeding in response to BTS messages targeting those behaviors ( 4 – 12 ). Likewise, the effects of displaying BTS messages pertaining to state move-over laws or warnings about possible animal crossings have had a very limited effect on speeds ( 13 , 14 ). However, other studies suggest that messages discouraging cell phone use or tailgating may yield some changes in those types of behaviors ( 3 , 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%